Problematika Kreativitas Anak Usia 5-6 Tahun dalam Kegiatan Menggambar Bebas - Tika Awalini; Setyo Yanuartuti; Indar Sabri (Syntax Literate, 2023)
The purpose of writing this article is to examine the problems that affect the creativity of children aged 5-6 years in drawing activities. This topic is important because children's creativity in drawing needs to be nurtured from an early age as a provision for them to be able to think critically and creatively when attending the next level of education. Many educators or parents do not understand the importance of drawing activities for children so that this activity is underestimated. Whereas through free drawing activities it can be seen that children have creative abilities which can be seen from how children express their ideas or imagination naturally without getting pressure from outside. The research conducted was library research using primary and secondary data sources, with data collection techniques: literature. Writing this article concludes that there are problems caused by two factors, namely internal and external factors that affect children's creativity in free drawing. On the internal factor there is the readiness of the child in learning and the introduction of tools, materials, media and free drawing techniques. While the external factors are factors that come from parents, the school environment, and also the social environment including the provision of motivation, creativity support facilities, and opportunities for exploration given to children